Root lignin composition and content in oil palm (Elaeis guineensis Jacq.) genotypes with different defense responses to Ganoderma boninense - Govender, Nisha; Abu-Seman, Idris; Mui-Yun, Wong (MDPI, 2020)
Basal stem rot of oil palms (OPs) is caused by Ganoderma boninense, a white-rot fungus. Root tissues are the primary route for G. boninense penetration and subsequent pathogenesis on OPs. Little is known on the host lignin biochemistry and selectivity for G. boninense degradation. Oil palm genotypes with different defense responses to G. boninense (highly tolerant, intermediately tolerant, and susceptible) were assessed for root lignin biochemistry (lignin content and composition), plant functional traits (height, fresh weight, girth), chlorophyll content, and root elemental nutrient content. One-year-old seedlings and five-year-old trees were screened for root thioglycolic acid lignin (TGA) content, lignin composition, and elemental nutrient depositions, while plant functional traits were evaluated in the one-year-old seedlings only. The TGA lignin in all the oil palm seedlings and trees ranged from 6.37 to 23.72 pM µg−1, whereas the nitrobenzene oxidation products showed a syringyl (S)-to-guaiacyl (G) ratios of 0.18–0.48. Tolerant genotypes showed significantly lower lignin content compared to the intermediately tolerant and susceptible genotypes. Likewise, the S/G ratio was higher in genotypes with lower lignin content. The depositions of root Fe, Si, Ti, S, and Cu were significantly different among the oil palm genotypes with the susceptible genotypes showing greater content than the tolerant genotypes.